1967
DOI: 10.2113/gssgfbull.s7-ix.6.909
|View full text |Cite
|
Sign up to set email alerts
|

Observations sur les structures internes et le developpement des Microcodium

Abstract: Algae, Eocene, France

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
4

Year Published

1978
1978
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 0 publications
0
6
0
4
Order By: Relevance
“…With regard to the smaller Microcodiimi (b) forms of Esteban (1972) which are possibly equivalent to the 'seed-plots' of Lucas & Montenat (1967) and Microrodiuni described by Montenat & Echallier (1977), their occurrence at the perimeter of rhizocretions or subjacent to root channel walls, displaying either a concentric arrangement in transverse sections or palisade rows in longitudinal sections, suggests an intimate relationship with plant root systems. They occur both in the Ancient and Recent.…”
Section: O M P a R I S O N S Between Ancient A N D Recent M I C R 0mentioning
confidence: 94%
See 3 more Smart Citations
“…With regard to the smaller Microcodiimi (b) forms of Esteban (1972) which are possibly equivalent to the 'seed-plots' of Lucas & Montenat (1967) and Microrodiuni described by Montenat & Echallier (1977), their occurrence at the perimeter of rhizocretions or subjacent to root channel walls, displaying either a concentric arrangement in transverse sections or palisade rows in longitudinal sections, suggests an intimate relationship with plant root systems. They occur both in the Ancient and Recent.…”
Section: O M P a R I S O N S Between Ancient A N D Recent M I C R 0mentioning
confidence: 94%
“…Because of this factor, Gottis (1963) suggested that Microcodium was an obligatory heterotroph. Lucas & Montenat (1967) overcame this problem by considering Microcodium to be the result of the activities of colonial bacteria. Wood & Basson (1972) state that the occurrence of their specimens and presence of chitin suggest that the organism could be a fungus.…”
Section: Biogenic Aspectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Los fósiles comunes en esta microfacies son: a) fungal fruiting bodies (Goldstein 1988, fig. 8B); b) cuerpos circulares con diámetros entre 30 y 50 µm, y cuerpos ovalados con tamaños entre 50 y 70 µm, que son reemplazados internamente por cristales de calcita espar radiales; corresponden a microcodium (Košir 2004;Lucas y Montenat 1967); c) cuerpos circulares con diámetro entre 20 y 40 µm, constituidos por un solo cristal de calcita espar; rodeados por un anillo constituido por cristales subrectangulares de calcita, corresponden a quistes de dinoflagelados calcáreos (Reháková 2000); d) cuerpos circulares con diámetros entre 20 y 40 µm; internamente son un solo cristal de calcita espar, rodeados por un anillo pardo oscuro, ocráceo, que corresponden a quistes de dinoflagelados calcáreos (Reháková 2000), y e) escasas conchillas de foraminíferos y, con menos frecuencia, fragmentos de bivalvos de hasta 60 μm. La presencia de cuarzo puede superar el 10 %; además, hay presencia de moscovita.…”
Section: Leyendaunclassified